2020
DOI: 10.1617/s11527-020-01571-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bio-stabilizers on capillary absorption and water vapour transfer into raw earth

Abstract: While raw earth can be used as a structural material, its water sensitivity limits its use in modern construction. Earth has a strong affinity with water. Both water imbibition and water vapour transfer have to be taken into consideration. This affinity can be a positive point to regulate indoor ambience, but it can also negatively affect earth's mechanical properties. To avoid this possible detrimental effect, bio-based additions are used all around the world to stabilize, protect from water and enhance the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 59 publications
0
27
0
Order By: Relevance
“…This soil has a plasticity index of 16.5%, a liquid limit of 46.2% and a plasticity limit of 29.7%. These soils were already studied in previous works (Guihéneuf et al, 2019;Menasria et al, 2017bMenasria et al, , 2017aPerrot et al, 2018;Guihéneuf et al, 2020bGuihéneuf et al, , 2020a.…”
Section: Soils and Additionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This soil has a plasticity index of 16.5%, a liquid limit of 46.2% and a plasticity limit of 29.7%. These soils were already studied in previous works (Guihéneuf et al, 2019;Menasria et al, 2017bMenasria et al, , 2017aPerrot et al, 2018;Guihéneuf et al, 2020bGuihéneuf et al, , 2020a.…”
Section: Soils and Additionsmentioning
confidence: 99%
“…Alternatively, the use of bio-based additions seems to be an interesting option. Some previous studies already highlighted that using bio-based additions in order to efficiently stabilize raw earth materials (Achenza and Fenu, 2006;Anger, 2011;Banakinao et al, 2016;Dove et al, 2016;Galán-Marín et al, 2010;Guihéneuf et al, 2020bGuihéneuf et al, , 2019Hafshejani et al, 2016;Menasria et al, 2017b;Nakamatsu et al, 2017;Ouedraogo, 2019;Vissac et al, 2017). This paper shows the ability of specific bio-based additions to increase the erosion resistance, which is a key parameter for both service ability and durability of compressed earth block (CEB).…”
Section: Introductionmentioning
confidence: 99%
“…Consolidants are then applied to the stone surface using techniques such as spraying, brushing or partial immersion, or mixed with other materials to yield composites [22]. Biopolymers alter mechanical properties of building materials and their water absorption and diffusion behavior, thus increasing cohesion and enhancing mechanical properties [23]. Bioconsolidation is also achieved by direct or indirect application of microorganisms and/or their metabolites [24].…”
Section: Bioconsolidation Techniquesmentioning
confidence: 99%
“…The incorporation of natural polymers for stabilizing earth has long been a practice embedded in construction traditions. The extensive research conducted over the past two decades has consistently demonstrated the capacity of these materials to enhance the mechanical properties, permeability, and water resistance of earth [ 66 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ].…”
Section: Introductionmentioning
confidence: 99%